Prenatal Gentle Yoga's Impact on the Length of the First Stage of Labor - Khalifatunnisak, Alfadefi; Khusmitha, Qatrunnada Naqiyyah (International Journal of Nursing and Midwifery Research, 2024)
Every woman hopes for a natural and painless delivery. The mother must make cautious preparations to have a pain-free, trauma-free delivery. It is possible to get ready for childbirth by making the woman physically and mentally prepared. To assist a pain-free delivery process, good physical health, a healthy uterus, and strong muscles in the birth canal are required. Prenatal gentle yoga is one method that pregnant women can prepare physically well. Prenatal yoga, also known as yoga for pregnant women, is a variation of hatha yoga tailored to the needs of expectant mothers and will help the mother's body adjust to the many changes that occur throughout pregnancy and childbirth. This study looked at the impact of prenatal gentle yoga on the length of the first stage of labor. This study is quantitative with an actual experiment, with simply a post-test. The participants in this study were all postpartum mothers who were part of a group of expectant women from various parts of Indonesia. A total of 40 participants from the study separate into two groups, the intervention group (consisting of 20 participants who practiced prenatal gentle yoga) and the control group. Prenatal gentle yoga and the length of the first stage, according to the results of data analysis using the Spearman rho test (p = 0.001, p < 0.05). This study's findings suggest mild prenatal yoga during pregnancy affects moms' first-stage labor duration. First stage duration is shorter in moms who practice prenatal gentle yoga, with an average that varies from 2 to 5 hours, compared to mothers who do not practice prenatal gentle yoga, with an average first stage duration of 8 to 10 hours.